Peran Kewirausahaan Sosial dalam Mengentaskan Persoalan Ekonomi di Masyarakat: Studi Literatur - Darliani, Ani; Wirda, Wirda (LPPM Universitas Multi Data Palembang, 2025)
Poverty is a fundamental issue that attracts the attention of governments worldwide, including Indonesia, which still has a high poverty rate. This study aims to analyze the role of entrepreneurship as a strategy to address poverty, which is complex and multidimensional, through a comprehensive and integrated approach. The research employs a qualitative approach using a literature review from various national and international sources related to poverty, entrepreneurship, and poverty alleviation strategies. The findings reveal that entrepreneurship plays a significant role in increasing income, empowering the economy, and creating job opportunities. Additionally, entrepreneurship utilizes local potential to promote inclusive and ustainable development